Low-carbon olefin additive for promoting heavy oil conversion, preparation method thereof, catalyst and hydrocarbon oil catalytic conversion method

By using a specific composition of low-carbon olefin additive in catalytic cracking, the problem of the increase in low-carbon olefin yield in the prior art has been solved, and the olefin content and diesel conversion efficiency in the liquefied gas are improved through improved combination of phosphorus-aluminum binder and molecular sieve.

CN119909746AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311436432.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

While improving the yield of low-carbon olefins in catalytic cracking, the prior art leads to a decrease in gasoline yield, and the structure of the β-molecular sieve is easily damaged during the mold release process and has poor selectivity.

Method used

A low-carbon olefin additive is provided, which contains 25-75% by weight of molecular sieve, 0.5-8% by weight of metal components, 3-40% by weight of phosphorus-aluminum binder, 1-25% by weight of other inorganic binder and 0-30% by weight of clay. Through specific composition and preparation methods, the content of propylene and butene in the liquefied gas is increased and diesel conversion is promoted.

Benefits of technology

Effectively increase the content of propylene and butene in the liquefied gas, increase the olefinity in LPG, promote diesel cracking, reduce gasoline loss, thereby reducing the sum of the yields of diesel and oil slurry, and increasing the sum of the yields of gasoline and LPG.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909746A_ABST
    Figure CN119909746A_ABST
Patent Text Reader

Abstract

The invention relates to a low-carbon olefin auxiliary agent for promoting heavy oil conversion and a preparation method thereof, a catalyst and a hydrocarbon oil catalytic conversion method, and the auxiliary agent contains 25-75 wt% of a molecular sieve, 0.5-8 wt% of a metal component in terms of metal oxide, and 3-40 wt% of a phosphorus-aluminum binder in terms of oxide based on the dry basis weight of the auxiliary agent, in terms of oxide, 1-25% by weight of other inorganic binder and 0-30% by weight of clay. The additive provided by the invention can effectively increase the content of propylene and butylene in catalytic cracking liquefied gas, improve the olefin degree in LPG, reduce the sum of the yields of diesel oil and oil slurry, and improve the sum of the yields of gasoline and LPG.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a low-carbon olefin auxiliary agent for promoting heavy oil conversion, a preparation method thereof, a catalyst and a method for catalytic conversion of hydrocarbon oil. Background Art

[0002] For most catalytic cracking units, adding catalysts is an effective technical approach to increase the production of light olefins, and the acidity of the catalyst and the shape-selective effect of the pores determine the yield of light olefins in the product.

[0003] Prior art discloses a five-membered ring high-silicon zeolite catalyst for light olefins in a fluidized catalytic device, the catalyst comprising (a) a five-membered ring high-silicon zeolite, (b) 8-24 wt% of phosphorus, as P2O5, based on particles containing the five-membered ring high-silicon zeolite, 1-10 wt% of iron oxide, as Fe2O3, located outside the five-membered ring high-silicon zeolite skeleton. The catalyst is fluidizable and has an average particle size of about 20 to about 200 microns. The catalyst composition can increase the yield of light olefins such as propylene in a fluidized catalytic cracking (FCC) process, but while increasing propylene, it will reduce the gasoline yield. The prior art discloses a cracking catalyst for increasing the concentration of propylene. The catalyst is composed of 10-65 wt% of a modified ZSM-5 molecular sieve, 0-60 wt% of clay, 15-60 wt% of an inorganic oxide binder, 0.5-15 wt% of a metal additive selected from one or more metals of Group VIIIB metals, and 2-25 wt% of a phosphorus additive on a dry basis. The modified ZSM-5 molecular sieve is modified with phosphorus and a metal selected from one of Fe, Co or Ni, and its anhydrous chemical expression, calculated as oxide, is (0-0.3)Na2O·(0.5-5)Al2O3·(1.3-10)P2O5·(0.7-15)M x O y (70-97)SiO2, x represents the number of atoms of M, y represents a number required to satisfy the oxidation state of M, and the metal additive and phosphorus additive are both calculated as oxides. The cracking catalyst is applied to the catalytic cracking process of petroleum hydrocarbons, and can significantly increase the propylene concentration in the liquefied gas while increasing the yield of catalytic cracking liquefied gas and the octane number of catalytic cracking gasoline, but the gasoline yield is significantly reduced, while diesel and oil slurry are not reduced.

[0004] The β molecular sieve has three mutually intersecting 12-membered ring channels, the 12-membered ring pore size of the one-dimensional channel parallel to the (001) crystal plane is 0.57-0.75 nm, and the 12-membered ring pore size of the other two-dimensional channel parallel to the (100) crystal plane is 0.56-0.65 nm. Due to the unique channel structure, high acidity and good hydrothermal stability of the β molecular sieve, its industrial application prospects are broad, and it has been successfully applied to petrochemical fields such as isomerization, catalytic cracking and alkylation of aromatics. The prior art discloses a β molecular sieve containing phosphorus and transition metals, a cracking aid for increasing the concentration of catalytic cracking light olefins and a preparation method thereof, and the aid is applied to catalytic cracking to increase the ethylene concentration in catalytic cracking dry gas and increase the concentration of propylene and isobutylene in liquefied gas. However, the main problems of the β molecular sieve in use are that on the one hand, its structure is easily damaged in the process of removing its template agent, and on the other hand, its catalyst propylene selectivity as an active component is poor. Summary of the invention

[0005] The purpose of the present invention is to provide a low-carbon olefin additive for promoting heavy oil conversion, a preparation method thereof, a catalyst and a method for catalytic conversion of hydrocarbon oil. The additive disclosed in the present invention can effectively increase the content of propylene and butene in liquefied gas, increase the olefin content in LPG, and at the same time promote diesel conversion and reduce gasoline loss.

[0006] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a light olefin auxiliary agent for promoting heavy oil conversion, wherein the auxiliary agent contains 25-75 wt% of molecular sieve, 0.5-8 wt% of metal component calculated as metal oxide, 3-40 wt% of phosphorus aluminum binder calculated as oxide, 1-25 wt% of other inorganic binder calculated as oxide and 0-30 wt% of clay;

[0007] The molecular sieve contains an MFI structure molecular sieve and a BEA structure molecular sieve, the molecular sieve contains a first phosphorus component, the phosphorus aluminum binder contains a second phosphorus component, the total content of the first phosphorus component and the second phosphorus component in the auxiliary agent calculated as P2O5 is 10-35% by weight; the pore volume of the auxiliary agent measured by the BJH method is greater than 0.12 mL / g;

[0008] Based on the total weight of the phosphate aluminum binder, the phosphate aluminum binder contains 3-15 weight % of Al2O3, 15-40 weight % of P2O5 and 0.1-10 weight % of a stabilizer; the P / Al weight ratio of the phosphate aluminum binder is 1.6-6, the pH value is 0.5-2.5, and QP0 2 / QP0 0 1-5, where QP0 2 Indicated by 31The chemical shift of the phosphorus aluminum binder obtained by P nuclear magnetic resonance spectroscopy is 12±2ppm, QP0 0 The peak area of ​​the resonance signal with a chemical shift of 0±2 ppm is represented, and the average particle size of the phosphorus aluminum binder is 10-30 nm.

[0009] Optionally, the phosphorus-aluminum binder contains 3-12 wt% Al2O3, 15-32 wt% P2O5 and 0.5-5 wt% stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.7-5.8, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 The solid content of the phosphorus aluminum binder is 15-50% by weight.

[0010] Optionally, based on the dry weight of the additive, the content of the molecular sieve is 30-65% by weight, the content of the metal component is 1-5% by weight, the content of the phosphoaluminum binder calculated as oxide is 8-32% by weight, the content of the other inorganic binder calculated as oxide is 2-20% by weight, and the content of the clay is 1-25% by weight.

[0011] Optionally, the other inorganic binder is selected from one or more of pseudo-boehmite, acidified aluminum stone, aluminum sol, silica-alumina sol and silica sol;

[0012] The clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth;

[0013] The MFI molecular sieve and the BEA structure molecular sieve are independently selected from one or more of hydrogen-type molecular sieves, phosphorus-containing molecular sieves, and phosphorus-containing and transition metal molecular sieves.

[0014] Preferably, the MFI structured molecular sieve is a multi-level pore ZSM-5 molecular sieve, the silicon-aluminum ratio of the multi-level pore ZSM-5 molecular sieve is 20-70, the pore volume of pores with a pore size of 2-50 nm accounts for 40-70% of the total pore volume; the pore volume of pores with a pore size of 2-20 nm accounts for more than 85% of the total mesopore volume, the pore volume measured by the BJH method is greater than 0.25 mL / g, and the micropore volume is greater than 0.1 cc / g;

[0015] Preferably, the BEA structure molecular sieve is a β molecular sieve, and the micropore specific surface area of ​​the β molecular sieve is 450-500m 2 / gram, the proportion of the mesopore volume of the beta molecular sieve to the total pore volume is 35-60 volume %; the proportion of the strong acid content of the molecular sieve to the total acid content is 25-55%, and the ratio of the B acid content to the L acid content is 35-75;

[0016] The weight ratio of the BEA structure molecular sieve to the MFI structure molecular sieve in the molecular sieve is (0.01-100): 1;

[0017] The metal in the metal component is selected from at least one of the Group VIII metals, preferably one or more of Fe, Co and Ni. The MFI structure molecular sieve and / or the BEA structure molecular sieve may contain a modified metal, wherein the modified metal contained is not included in the metal component, but is regarded as a part of the molecular sieve component. Preferably, the total content of the modified metal and the metal component in the molecular sieve is 0.5-8% by weight.

[0018] The second aspect of the present disclosure provides a method for preparing the low-carbon olefin auxiliary agent provided in the first aspect of the present disclosure, the method comprising:

[0019] S1, mixing the molecular sieve, the other inorganic binder, the clay, the metal source and water, and controlling the pH value of the slurry to be greater than 2.5 to obtain a first slurry;

[0020] S2. After mixing the first slurry with the phosphorus aluminum binder, spray drying and calcining are performed to obtain the auxiliary agent.

[0021] Optionally, the aluminum-phosphorus binder is prepared by a method comprising the following steps:

[0022] (1) mixing an aluminum source, water and a stabilizer at 50-95° C. with stirring to obtain an aluminum oxide precursor solution having a solid content of 5-40 wt %;

[0023] (2) Mixing and reacting the alumina precursor solution with phosphate at a temperature of 25-70° C. and under stirring conditions to obtain the phosphate-aluminum binder.

[0024] Optionally, the aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride;

[0025] The phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate;

[0026] The stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid;

[0027] The metal source is one or more of iron salt, cobalt salt and nickel salt, preferably FeCl3·6H2O. The third aspect of the present disclosure provides a catalyst, which contains an auxiliary agent and an optional main catalyst, and the auxiliary agent is the auxiliary agent provided in the first aspect of the present disclosure.

[0028] A fourth aspect of the present disclosure provides a method for catalytic conversion of hydrocarbon oil, the method comprising: contacting the hydrocarbon oil with the auxiliary agent provided by the first aspect of the present disclosure or the catalyst provided by the third aspect to react.

[0029] Optionally, the reaction conditions include: temperature of 300-700°C, weight hourly space velocity of 4-120 hours -1 , the agent-oil weight ratio is 1-20.

[0030] Through the above technical solution, the auxiliary agent disclosed in the present invention contains a specific phosphorus-aluminum binder, which has less free phosphate and more polymerized phosphate, good bonding performance and long service life. The phosphorus-aluminum binder has a synergistic effect with the molecular sieve, so that the auxiliary agent disclosed in the present invention can effectively increase the content of propylene and butene in liquefied gas, increase the olefin content in LPG, promote diesel cracking, reduce gasoline loss, thereby reducing the sum of the yields of diesel and slurry oil, and increasing the sum of the yields of gasoline and LPG.

[0031] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0033] Figure 1 It is the nuclear magnetic resonance spectrum of the phosphate aluminum binder prepared in Example 1 of the present disclosure and the nuclear magnetic resonance spectrum of the phosphate aluminum binder prepared in Comparative Example 1. DETAILED DESCRIPTION

[0034] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0035] The first aspect of the present disclosure provides a low-carbon olefin additive for promoting heavy oil conversion, wherein the additive contains, based on the dry weight of the additive, 25-75 wt% of a molecular sieve, 1-8 wt% of a metal component calculated as metal oxide, 3-40 wt% of a phosphorus aluminum binder calculated as oxide, 1-25 wt% of other inorganic binders calculated as oxide, and 0-30 wt% of clay;

[0036] The molecular sieve contains an MFI structure molecular sieve and a BEA structure molecular sieve, the molecular sieve contains a first phosphorus component, the phosphorus aluminum binder contains a second phosphorus component, the total content of the first phosphorus component and the second phosphorus component in the auxiliary agent calculated as P2O5 is 10-35% by weight; the pore volume of the auxiliary agent measured by the BJH method is greater than 0.12 mL / g;

[0037] Based on the total weight of the phosphate aluminum binder, the phosphate aluminum binder contains 3-15 weight % of Al2O3, 15-40 weight % of P2O5 and 0.1-10 weight % of a stabilizer; the P / Al weight ratio of the phosphate aluminum binder is 1.6-6, the pH value is 0.5-2.5, and QP0 2 / QP0 0 1-5, where QP0 2 Indicated by 31 The chemical shift of the phosphorus aluminum binder obtained by P nuclear magnetic resonance spectroscopy is 12±2ppm, QP0 0 The peak area of ​​the resonance signal with a chemical shift of 0±2 ppm is represented, and the average particle size of the phosphorus aluminum binder is 10-30 nm.

[0038] The auxiliary agent disclosed in the present invention contains a specific phosphorus-aluminum binder, which has less free phosphate and more polymerized phosphate, good bonding performance and long service life, and can reduce the interaction with aluminum in the molecular sieve, which is beneficial to improving the activity and hydrothermal stability of the molecular sieve. The phosphorus-aluminum binder has a synergistic effect with the molecular sieve, can effectively increase the content of propylene and butene in gasoline, increase the olefin content in LPG, and promote heavy oil conversion, reduce the yield of diesel and oil slurry, and increase the yield of gasoline and LPG.

[0039] In the present disclosure, the pore volume and total pore volume measured by the BJH method refer to the pore volume measured by the nitrogen adsorption capacity method; for specific methods, refer to the pore volume and pore size distribution measured by the nitrogen adsorption capacity method of RIPP151-90.

[0040] According to the present disclosure, the average particle size of the phosphate-aluminum binder is detected by a transmission electron microscopy method, specifically, the phosphate-aluminum binder is subjected to a transmission electron microscopy analysis, 100 phosphate-aluminum binder particles are randomly selected from the TEM photo and their maximum diameters are respectively measured as their particle sizes, and the average value of the particle sizes of the 100 phosphate-aluminum binder particles is calculated, which is the average particle size.

[0041] In a preferred embodiment of the present disclosure, the phosphorus-aluminum binder contains 3-12 wt% Al2O3, 15-32 wt% P2O5 and 0.1-5 wt% stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.7-5.8, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 It is 1.5-5.

[0042] In a specific embodiment of the present disclosure, the solid content of the phosphorus aluminum binder is 15-50 wt %, preferably 20-45 wt %.

[0043] In a specific embodiment of the present disclosure, based on the dry weight of the additive, the content of the molecular sieve is 30-65% by weight, the content of the metal component is 1-5% by weight, the content of the phosphorus aluminum binder calculated as oxide is 8-32% by weight, the content of the other inorganic binder calculated as oxide is 2-20% by weight, and the content of the clay is 1-25% by weight; more preferably, the content of the molecular sieve is 40-60% by weight, the content of the metal component is 0.5-5% by weight, the content of the phosphorus aluminum binder calculated as oxide is 20-30% by weight, the content of the other inorganic binder calculated as oxide is 10-18% by weight, and the content of the clay is 5-10% by weight. The additive having the above composition has better catalytic performance, can further improve the yield of light olefins, promote the conversion of heavy oil, and reduce coke and oil slurry.

[0044] In a specific embodiment of the present disclosure, the total content of the first phosphorus component and the second phosphorus component in the additive calculated as P2O5 is 15-25 wt %; the pore volume of the additive measured by the BJH method is 0.12-0.14 mL / g.

[0045] According to the present disclosure, other inorganic binders can be commonly used by those skilled in the art in preparing catalysts. In a specific embodiment of the present disclosure, the other inorganic binder is one or more selected from pseudo-boehmite, diaspore, aluminum sol, silica-alumina sol and silica sol.

[0046] According to the present disclosure, clay can be commonly used by those skilled in the art in preparing catalysts. In a specific embodiment of the present disclosure, the clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth.

[0047] According to the present disclosure, the MFI structure molecular sieve and the BEA structure molecular sieve are independently selected from one or more of hydrogen-type molecular sieves, phosphorus-containing molecular sieves, and phosphorus- and transition metal-containing molecular sieves. In one embodiment, at least one of the MFI structure molecular sieve and the BEA structure molecular sieve contains phosphorus; preferably, the MFI structure molecular sieve and the BEA structure molecular sieve are independently molecular sieves containing phosphorus and transition metals, that is, the MFI structure molecular sieve can contain phosphorus and transition metals at the same time, and the BEA structure molecular sieve can contain phosphorus and transition metals at the same time.

[0048] In a preferred specific embodiment, the MFI structured molecular sieve is a multi-level pore ZSM-5 molecular sieve, the silicon-aluminum ratio of the multi-level pore ZSM-5 molecular sieve is 20-70, the pore volume measured by the BJH method is greater than 0.25 mL / g, the pore volume of pores with a pore diameter of 2-50 nm accounts for 40-70% of the total pore volume; the pore volume of pores with a pore diameter of 2-20 nm accounts for more than 85% of the total mesopore volume, and the micropore volume is greater than 0.1 cc / g.

[0049] In a preferred embodiment, the BEA structure molecular sieve is a β molecular sieve, and the micropore specific surface area of ​​the β molecular sieve is 450-500m 2 / g, the proportion of the mesopore volume of the β molecular sieve to the total pore volume is 35-60 volume %; the proportion of the strong acid content of the molecular sieve to the total acid content is 25-55%, and the ratio of the B acid content to the L acid content is 35-75.

[0050] According to the present disclosure, the pore volume, total pore volume and micropore volume determined by the BJH method are the pore volumes measured according to the RIPP 151-90 method (see Petrochemical Analysis Methods, Nitrogen Adsorption Capacitance Method for Determination of Pore Volume and Pore Size Distribution of Catalysts, edited by Yang Cuiding et al., Petrochemical Analysis Methods (RIPP Experimental Methods), Science Press, 1990).

[0051] In a specific embodiment of the present disclosure, the weight ratio of the BEA structure molecular sieve to the MFI structure molecular sieve is (0.01-100): 1, preferably (0.1-30): 1, and more preferably (0.25-6): 1. When the molecular sieve adopts the BEA structure molecular sieve and the MFI structure molecular sieve in the above ratio, the additive can further increase the content of propylene and butene in the liquefied gas, increase the olefin degree in LPG, promote diesel cracking, reduce gasoline loss, thereby reducing the sum of the yields of diesel and slurry oil, and increasing the sum of the yields of gasoline and LPG.

[0052] According to the present disclosure, the metal in the metal component is selected from at least one of Group VIII metals, preferably one or more of Fe, Co and Ni.

[0053] The second aspect of the present disclosure provides a method for preparing the auxiliary agent provided in the first aspect of the present disclosure, the method comprising: S1, mixing and slurrying the molecular sieve, the other inorganic binder, the clay, the metal source and water, controlling the pH value of the slurry to be greater than 2.5, to obtain a first slurry; S2, mixing the first slurry with the phosphate aluminum binder, spray drying and calcining to obtain the auxiliary agent.

[0054] The method disclosed in the present invention can prepare an additive with better catalytic performance, which can effectively increase the content of propylene and butene in catalytic cracking liquefied gas, improve the olefin degree in LPG, reduce the yield of diesel and slurry oil, and increase the sum of the yield of gasoline and LPG.

[0055] In a specific embodiment of the present disclosure, in step S1, the molecular sieve, the clay and water are first mixed and slurried, and then the other inorganic binder is added to the obtained mixture for mixing and slurrying to obtain the first slurry, which is beneficial to further improve the activity and strength of the additive.

[0056] According to the present disclosure, spray drying is a technical means well known to those skilled in the art, and the specific method is not repeated here. In a specific embodiment, the inlet temperature of spray drying can be 300-700°C, and the outlet temperature can be 80-200°C.

[0057] In a specific embodiment of the present disclosure, the calcination temperature is 400-700° C., preferably 450-600° C., and the calcination time is 0.5-100 hours, preferably 0.5-10 hours.

[0058] In a specific embodiment of the present disclosure, the phosphorus-aluminum binder is prepared by a method comprising the following steps: (1) mixing an aluminum source, water and a stabilizer at 50-95° C. under stirring conditions to obtain an aluminum oxide precursor solution having a solid content of 5-40% by weight; (2) mixing and reacting the aluminum oxide precursor solution with phosphate at a temperature of 25-70° C. under stirring conditions to obtain the phosphorus-aluminum binder. In one embodiment, in step (2), the time of the mixing reaction can vary within a wide range, as long as the aluminum oxide precursor solution and the phosphate can form a transparent colloid after the mixing reaction, for example, it can be 10-60 minutes.

[0059] The phosphate-aluminum binder used in the method disclosed in the present invention is prepared from low-cost aluminum salts and phosphates. The phosphate-aluminum binder has a small amount of free phosphate and a large amount of highly polymerized phosphate, and has good bonding properties. The stabilizer contained in the binder can effectively extend the service life of the phosphate-aluminum binder.

[0060] In a specific embodiment of the present disclosure, the aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride; the phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate; the stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid; the metal source contains a soluble metal salt of a Group VIII metal, for example, it can be one or more of an iron salt, a cobalt salt and a nickel salt, preferably FeCl3·6H2O.

[0061] The third aspect of the present disclosure provides a catalyst, which contains an auxiliary agent and an optional main catalyst, wherein the auxiliary agent is the auxiliary agent provided in the first aspect of the present disclosure.

[0062] According to the present disclosure, the main catalyst can be selected according to actual needs and can be a catalytic cracking catalyst and / or catalytic cracking catalyst well known to those skilled in the art.

[0063] The fourth aspect of the present disclosure provides a method for catalytic conversion of hydrocarbon oil, which comprises: contacting the hydrocarbon oil with the auxiliary agent provided by the first aspect of the present disclosure or the catalyst provided by the third aspect of the present disclosure for reaction.

[0064] In a specific embodiment of the present disclosure, the reaction conditions include: a temperature of 300-700°C, preferably 400-600°C, more preferably 400-550°C, a weight hourly space velocity of 4-120 hours -1 , preferably 4-80 hours -1 , more preferably 8-16 hours -1 , the weight ratio of catalyst to oil is 1-20, preferably 2-10, more preferably 4-8. The additive provided by the present disclosure can be used in various existing catalytic cracking reactors, such as fixed bed reactors, fluidized bed reactors, riser reactors, multi-reaction zone reactors, etc.

[0065] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.

[0066] When the additive disclosed in the present invention is used for evaluating the performance of catalytic cracking reaction, an ACE device is used for evaluation.

[0067] The RIPP standard method described in the present disclosure can be specifically found in "Petrochemical Analysis Methods", edited by Yang Cuiding et al., 1990 edition.

[0068] The pore volume was determined by nitrogen adsorption method (RIPP151-90).

[0069] The properties of some of the raw materials used in the embodiments and comparative examples are as follows:

[0070] Pseudo-boehmite is an industrial product produced by Shandong Aluminum Company, with a solid content of 60% by weight;

[0071] Alumina sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with an Al2O3 content of 21.5% by weight;

[0072] The kaolin is a special kaolin for additives produced by Suzhou Kaolin Company, with a solid content of 78% by weight.

[0073] FeCl3·6H2O: chemically pure, purity 99%, Xilong Scientific Co., Ltd.

[0074] Hydrochloric acid: chemically pure, concentration 36-38% by weight, produced by Beijing Chemical Plant.

[0075] MPZ molecular sieve: an industrial product produced by Sinopec Catalyst Qilu Branch, with a P2O5 content of 7.25% by weight, a Fe2O3 content of 1.95% by weight, and a crystallinity of 72%.

[0076] Phosphorus-containing β molecular sieve: The H-β molecular sieve was impregnated with a 0.2 mol / L diammonium phosphate solution by a saturated impregnation method with stirring for two hours, dried at 120°C for 10 hours, and calcined at 500°C for 3 hours to obtain a phosphorus-modified β molecular sieve P-β, in which the P2O5 content was 6.23% by mass and the crystallinity was 78%.

[0077] Catalytic cracking catalyst SLA is a catalytic cracking catalyst produced by Sinopec Catalyst Qilu Branch.

[0078] The average particle size of the phosphorus aluminum binder disclosed in the present invention is detected by transmission electron microscopy.

[0079] Preparation Examples 1-4 are preparation examples of the phosphoaluminum binder disclosed in the present invention.

[0080] Preparation Example 1

[0081] (1) 0.56 kg of anhydrous aluminum sulfate, 0.25 kg of deionized water, and 0.05 kg of oxalic acid were mixed and stirred, and the mixture was heated to 70° C. and slurried for 30 minutes to obtain an aluminum oxide precursor solution having a solid content of 39 wt %;

[0082] (2) Control the temperature to 45°C and add 0.56 kg of ammonium dihydrogen phosphate to the alumina precursor solution prepared in step (1) under stirring, and then react at 45°C for 45 minutes until the mixture becomes a transparent colloid to obtain a phosphorus-aluminum binder P-1. The material ratio is shown in Table 1, and the nuclear magnetic resonance spectrum of the phosphorus-aluminum binder is shown in Figure 1 .

[0083] Preparation Example 2-4

[0084] The phosphorus aluminum binder was prepared by the same method as in Preparation Example 1, the only difference being the raw materials used and their amounts. The specific material ratios are shown in Table 1.

[0085] Preparation Comparative Example 1

[0086] The phosphorus-aluminum inorganic binder is prepared according to the method provided by patent ZL201110180891.X. The specific method is as follows:

[0087] At room temperature (25°C), 0.98 kg of pseudo-boehmite (containing 0.6 kg of Al2O3), 0.2 kg of rectorite (0.16 kg on a dry basis) and 0.44 kg of deionized water were mixed and slurried for 30 minutes. 2.01 kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring at a rate of 0.03 kg of phosphoric acid / min / kg of alumina source. The temperature was raised to 70°C and then reacted at this temperature for 45 minutes to obtain a phosphorus-aluminum inorganic binder DPAL-1. The NMR spectrum is shown in Figure 1 .

[0088] Depend on Figure 1 It can be seen that in the 31P nuclear magnetic resonance spectrum of the phosphorus aluminum binder, the peak area of ​​the resonance signal with a chemical shift of 12±2ppm is defined as QP0 2 The peak area of ​​the resonance signal with a chemical shift of 0±2ppm is defined as QP0 0 At the same phosphorus-aluminum ratio, the QP0 of the phosphorus-aluminum binder prepared in Preparation Example 1 is 2 / QP0 0 Compared with the QP0 of the phosphorus aluminum inorganic binder prepared in Comparative Example 1 2 / QP0 0 Higher, indicating a higher degree of polymerization.

[0089] Table 1

[0090]

[0091]

[0092] Examples 1-6 are preparation examples of the auxiliary agent disclosed in the present invention.

[0093] Example 1

[0094] S1. Take P-β molecular sieve and MPZ molecular sieve, add decationized water and beat for 10 minutes, beat for 120 minutes to obtain molecular sieve slurry; add kaolin, aluminum sol, FeCl3·6H2O and pseudo-boehmite to decationized water and beat for 20 minutes, add molecular sieve slurry under stirring, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue beating for 45 minutes to obtain the first slurry;

[0095] S2. Add the phosphorus aluminum binder P-1 to the first slurry prepared in step S1, stir for 5 minutes, spray dry the obtained slurry, and calcine the obtained microspheres at 500° C. for 2 hours to obtain the auxiliary agent CAT-1. The proportion is shown in Table 2.

[0096] Embodiment 2-6

[0097] The auxiliary agent was prepared by the same method as in Example 1, except that different raw materials and their amounts were used. The specific ratios are shown in Table 2.

[0098] Comparative Example 1

[0099] Take MPZ molecular sieve, kaolin, FeCl3·6H2O and pseudo-boehmite, add decationized water and aluminum sol to slurry for 120 minutes, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to slurry for 45 minutes, then add phosphate aluminum inorganic binder (DPAL-1), stir for 5 minutes, and then spray dry the obtained slurry to obtain microspheres. The microspheres are calcined at 500°C for 1 hour to obtain the additive DCAT-1. The proportion is shown in Table 2.

[0100] Comparative Example 2

[0101] The additive DCAT-2 was prepared in the same manner as in Example 1, except that the phosphorus-aluminum inorganic binder DPAL-1 was used instead of the phosphorus-aluminum binder P-1. The material ratio and parameters of the additive are shown in Table 2.

[0102] Comparative Example 3

[0103] The auxiliary agent DCAT-3 was prepared by the same method as in Example 1, except that, as shown in Table 2, an equal amount of MPZ molecular sieve was used instead of P-β molecular sieve in step S1.

[0104] Table 2

[0105]

[0106] Test Case

[0107] The following examples take a fixed fluidized bed reactor as an example to illustrate the cracking reaction effect of the cracking catalyst provided by the present disclosure.

[0108] Catalytic cracking catalyst SLA and 30g CAT-1-6 and DCAT-1-3 were aged for 17 hours at 800°C and 100% steam atmosphere. Different amounts of the aged catalysts were mixed with SLA (main properties are shown in Table 3), and the catalyst mixture was loaded into the reactor of a small fixed fluidized bed reactor to catalytically crack the crude oil shown in Table 4. Table 5 shows the reaction conditions and reaction results.

[0109] Table 3 Main properties of catalytic cracking catalyst SLA

[0110]

[0111] Table 4 Evaluation of the properties of the feedstock oil

[0112]

[0113]

[0114] Table 5 Evaluation results

[0115]

[0116]

[0117]

[0118] It can be seen from Table 5 that, compared with the reference catalyst, the additive provided by the present disclosure can effectively increase the content of propylene and butene in catalytic cracking liquefied gas, improve the olefin degree in LPG, reduce the sum of the yields of diesel and slurry oil, and increase the sum of the yields of gasoline and LPG.

[0119] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0120] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0121] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A low-carbon olefin additive for promoting heavy oil conversion, which comprises, based on the dry weight of the additive, 25-75 wt% of a molecular sieve, 0.5-8 wt% of a metal component calculated as metal oxide, 3-40 wt% of a phosphorus aluminum binder calculated as oxide, 1-25 wt% of other inorganic binders calculated as oxide, and 0-30 wt% of clay; in, The molecular sieve contains an MFI structure molecular sieve and a BEA structure molecular sieve, the molecular sieve contains a first phosphorus component, the phosphorus aluminum binder contains a second phosphorus component, the total content of the first phosphorus component and the second phosphorus component in the auxiliary agent calculated as P2O5 is 10-35% by weight; the pore volume of the auxiliary agent measured by the BJH method is greater than 0.12 mL / g; Based on the total weight of the phosphate aluminum binder, the phosphate aluminum binder contains 3-15 weight % of Al2O3, 15-40 weight % of P2O5 and 0.1-10 weight % of a stabilizer; the P / Al weight ratio of the phosphate aluminum binder is 1.6-6, the pH value is 0.5-2.5, and QP0 2 / QP0 0 1-5, where QP0 2 Indicated by 31 The chemical shift of the aluminum-phosphorus binder detected by P nuclear magnetic resonance spectroscopy is 12±2ppm, and the resonance signal peak area is QP0 0 The peak area of ​​the resonance signal with a chemical shift of 0±2 ppm is represented, and the average particle size of the phosphorus aluminum binder is 10-30 nm.

2. The auxiliary agent according to claim 1, wherein The phosphate aluminum binder contains 3-12 wt% Al2O3, 15-32 wt% P2O5 and 0.5-5 wt% stabilizer; the P / Al weight ratio of the phosphate aluminum binder is 1.7-5.8, the pH value is 0.5-2.5, QP0 2 / QP0 0 The solid content of the phosphorus aluminum binder is 15-50% by weight.

3. The auxiliary agent according to claim 1, wherein Based on the dry weight of the additive, the content of the molecular sieve is 30-65% by weight, the content of the metal component is 1-5% by weight, the content of the phosphate aluminum binder calculated as oxide is 8-32% by weight, the content of the other inorganic binder calculated as oxide is 2-20% by weight, and the content of the clay is 1-25% by weight.

4. The auxiliary agent according to claim 1, wherein The other inorganic binder is selected from one or more of pseudo-boehmite, acidified aluminum stone, aluminum sol, silica-alumina sol and silica sol; The clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth; The molecular sieves are MFI structure molecular sieves and BEA structure molecular sieves; the MFI molecular sieves and the BEA molecular sieves are independently selected from one or more of hydrogen molecular sieves, phosphorus-containing molecular sieves and transition metal-containing molecular sieves; Preferably, the MFI structured molecular sieve is a multi-level pore ZSM-5 molecular sieve, the silicon-aluminum ratio of the multi-level pore ZSM-5 molecular sieve is 20-70, the pore volume of pores with a pore size of 2-50 nm accounts for 40-70% of the total pore volume; the pore volume of pores with a pore size of 2-20 nm accounts for more than 85% of the total mesopore volume, the pore volume measured by the BJH method is greater than 0.25 mL / g, and the micropore volume is greater than 0.1 cc / g; Preferably, the BEA structure molecular sieve is a β molecular sieve, and the micropore specific surface area of ​​the β molecular sieve is 450-500m 2 / gram, the proportion of the mesopore volume of the beta molecular sieve to the total pore volume is 35-60 volume %; the proportion of the strong acid content of the molecular sieve to the total acid content is 25-55%, and the ratio of the B acid content to the L acid content is 35-75; The weight ratio of the BEA structure molecular sieve to the MFI structure molecular sieve in the molecular sieve is (0.01-100): 1; The metal in the metal component is selected from at least one of the Group VIII metals, preferably one or more of Fe, Co and Ni.

5. A method for preparing the low-carbon olefin additive according to any one of claims 1 to 4, the method comprising: S1, mixing the molecular sieve, the other inorganic binder, the clay, the metal source and water, and controlling the pH value of the slurry to be greater than 2.5 to obtain a first slurry; S2. After mixing the first slurry with the phosphorus aluminum binder, spray drying and calcining are performed to obtain the auxiliary agent.

6. The method according to claim 5, wherein: The aluminum-phosphorus binder is prepared by a method comprising the following steps: (1) mixing an aluminum source, water and a stabilizer at 50-95° C. with stirring to obtain an aluminum oxide precursor solution having a solid content of 5-40 wt %; (2) Mixing and reacting the alumina precursor solution with phosphate at a temperature of 25-70° C. and under stirring conditions to obtain the phosphate-aluminum binder.

7. The method according to claim 6, wherein: The aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride; The phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate; The stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid; The metal source is one or more of iron salt, cobalt salt and nickel salt, preferably FeCl3·6H2O.

8. A catalyst, comprising an auxiliary agent and an optional main catalyst, wherein the auxiliary agent is the auxiliary agent according to any one of claims 1 to 4.

9. A method for catalytic conversion of hydrocarbon oil, the method comprising: The hydrocarbon oil is contacted with the auxiliary agent according to any one of claims 1 to 4 or the catalyst according to claim 8 to react.

10. The method according to claim 9, wherein: The reaction conditions include: temperature of 300-700°C, weight hourly space velocity of 4-120 hours -1 , the agent-oil weight ratio is 1-20.

Citation Information

Patent Citations

  • Inorganic binder containing phosphorus and aluminum compounds

    CN102847547B

  • Cracking aid for improving lower-carbon olefin concentration

    CN102847552A

  • Cracking auxiliary agent for increasing low-carbon olefin concentration

    CN103785456A

  • Catalytic cracking assistant capable of increasing concentration of low-carbon olefin and preparation method for catalytic cracking assistant

    CN105013526A

  • Crystalline aluminophosphate compositions

    US5051246A